Structure of the VipA/B type VI secretion complex suggests a contraction-state-specific recycling mechanism - Kube, Sebastian; Kapitein, Nicole; Mogk, Axel (Cell reports, 2014)
The bacterial type VI secretion system is a multicomponent molecular machine directed against eukaryotic host cells and competing bacteria. An intracellular contractile tubular structure that bears functional homology with bacteriophage tails is pivotal for ejection of pathogenic effectors. Here, we present the 6 Å cryoelectron microscopy structure of the contracted Vibrio cholerae tubule consisting of the proteins VipA and VipB. We localized VipA and VipB in the protomer and identified structural homology between the C-terminal segment of VipB and the tail-sheath protein of T4 phages. We propose that homologous segments in VipB and T4 phages mediate tubule contraction. We show that in type VI secretion, contraction leads to exposure of the ClpV recognition motif, which is embedded in the type VI-specific four-helix-bundle N-domain of VipB. Disaggregation of the tubules by the AAA+ protein ClpV and recycling of the VipA/B subunits are thereby limited to the contracted state.